TMT-Based Plasma Proteomics Reveals Dyslipidemia Among Lowlanders During Prolonged Stay at High Altitudes - Pooja,; Sharma, Vandana; Meena, Ram Niwas; Ray, Koushik; Panjwani, Usha; Varshney, Rajeev; Sethy, Niroj Kumar (Frontiers in Physiology, 2021)
Acute exposure to high altitude perturbs physiological parameters and induces an array of molecular changes in healthy lowlanders. However, activation of compensatory mechanisms and biological processes facilitates high altitude acclimatization. A large number of lowlanders stay at high altitude regions from weeks to months for work and professional commitments and thus are vulnerable to altitude associated disorders. Despite this, there is a scarcity of information for molecular changes associated with long term stay at high altitude. In the present study, we evaluated oxygen saturation (SpO2), heart rate (HR), systolic and diastolic blood pressure (SBP and DBP) of lowlanders after short- (7 days, HA-D7) and long-term (3 months, HA-D150) stay at high altitude and used TMT-based proteomics studies to decipher plasma proteome alterations. We observed improvements in SpO2 levels after prolonged stay while HR, SBP and DBP remained elevated as compared to short-term stay. Plasma proteomics studies revealed higher levels of apolipoproteins APOB, APOCI, APOCIII, APOE and APOL and carbonic anhydrases (CA1 and CA2) during hypoxia exposure. Biological network analysis also identified profound alterations in lipoprotein-associated pathways like plasma lipoprotein assembly, VLDL clearance, chylomicron assembly, chylomicron remodeling, plasma lipoprotein clearance and chylomicron clearance. In corroboration, lipid profiling revealed higher levels of total cholesterol (TC), triglycerides (TGs), low density lipoprotein (LDL) for HA-D150 while high density lipoproteins (HDL) levels were lower as compared to HA-D7 and sea level indicating dyslipidemia. We also observed higher levels of pro-inflammatory cytokines IL-6, TNFα and CRP for HA-D150 along with oxidized LDL (oxLDL) suggesting vascular inflammation and pro-artherogenic propensity. These results demonstrate that long-term stay at high altitude exacerbate dyslipidemia and associated disorders.